Predicting indoor air quality (IAQ) on naval ship: a contour mapping approach to air distribution - Awang, Mohd Naim; Zahaba, Maryam; Azmir, Nor Azali (GLOBAL ACADEMIC EXCELLENCE (M) SDN BHD, 2024)
Abstract: Ships often report poor indoor air quality (IAQ) due to their enclosed and confined spaces. The main factor contributing to poor IAQ onboard was the inefficiency of the heating, ventilation, and air conditioning (HVAC) systems. Poor IAQ adversely affects the health of the crew, which can indirectly cause Sick Boat syndrome (SBoS). Therefore, close monitoring of HVAC efficiency and IAQ on naval ships is crucial, as these vessels serve as the operational homes for our nation's front liners. This paper aims to analyse air distribution from the HVAC system by simulating the temperature, carbon dioxide (CO₂), and particulate matter (PM2.5) within the designated ship’s compartment. Using NoiseAtWork software, a contour mapping method was employed to visualise the spatial distribution of selected IAQ parameters. Before that, real-time sampling of selected IAQ parameters was done on the bridge. The contour map of the air distribution revealed that open hatches affected the dispersion of CO₂ and PM2.5, leading to variations in concentration contours within the area. PM2.5 map showed PM2.5 accumulation, possibly due to old dust from the ducting and diffusers. Although temperature distribution was even, it did not comply with ICOP IAQ 2010 standards. This study underscores the importance of air distribution prediction, thus highlighting the necessity for crew adherence to the best practices, such as closing the hatch, and perform maintenance including ducting cleaning as recommended by the design systems or the class society to maintain healthy indoor environments. Therefore, by using NoiseAtWork, the contour mapping method can help to predict the influence of HVAC efficiency and operational practices on IAQ. This method is valuable for identifying the optimal HVAC component configurations such as the best location of an air diffuser for the new shipbuilding project. Ensuring proper air circulation throughout the ship will enhance HVAC system efficiency and improve the IAQ onboard.